1993
DOI: 10.1136/jech.47.3.229
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic delay, clinical stage, and social class: a hospital based study.

Abstract: Study objective-To measure delay in admission to a large hospital and to study the Measurements and main results-After patient interview and discharge from hospital, the clinical record was consulted for information on the length of stay and the diagnosis, and in particular for the staging of hernia or colon cancer (according to the protocol of the Jefferson Medical College). Multiple logistic regression was used to estimate odds ratios and 95% confidence intervals. There was an association between advanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
2
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 14 publications
1
13
2
1
Order By: Relevance
“…For stomach cancer, the range is 3-51% (Mikulin and Hardcastle, 1987;Haugstvedt et al, 1991;Wile et al, 1993) (70% in our sample). However, some authors cover all non-elective admissions (Holliday and Hardcastle, 1979;Nilsson et al, 1982;Brown et al, 1983;MacArthur and Smith, 1984;Mikulin and Hardcastle, 1987;Fielding et al, 1989;Ratcliffe et al, 1989;Haugstvedt et al, 1991;Porta et al, 1991;Anderson et al, 1992;Hargarten et al, 1992;Vineis et al, 1993;Wile et al, 1993;Curless et al, 1994;Mountney et al, 1994;Mulcahy et al, 1994;Scott et al, 1995) (as in the present study), while others distinguish urgent from true emergencies (Heys et al, 1994;West and Rosen, 1996).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…For stomach cancer, the range is 3-51% (Mikulin and Hardcastle, 1987;Haugstvedt et al, 1991;Wile et al, 1993) (70% in our sample). However, some authors cover all non-elective admissions (Holliday and Hardcastle, 1979;Nilsson et al, 1982;Brown et al, 1983;MacArthur and Smith, 1984;Mikulin and Hardcastle, 1987;Fielding et al, 1989;Ratcliffe et al, 1989;Haugstvedt et al, 1991;Porta et al, 1991;Anderson et al, 1992;Hargarten et al, 1992;Vineis et al, 1993;Wile et al, 1993;Curless et al, 1994;Mountney et al, 1994;Mulcahy et al, 1994;Scott et al, 1995) (as in the present study), while others distinguish urgent from true emergencies (Heys et al, 1994;West and Rosen, 1996).…”
Section: Discussionmentioning
confidence: 94%
“…The proportion of colorectal cancer patients with an emergency presentation has been reported to vary from 11% to 50% (Holliday and Hardcastle, 1979;Nilsson et al, 1982;Fielding et al, 1989;Ratcliffe et al, 1989;Porta et al, 1991;Anderson et al, 1992;Hargarten et al, 1992;Vineis et al, 1993;Curless et al, 1994;Heys et al, 1994;Mulcahy et al, 1994;Mountney et al, 1994;Scott et al, 1995). For stomach cancer, the range is 3-51% (Mikulin and Hardcastle, 1987;Haugstvedt et al, 1991;Wile et al, 1993) (70% in our sample).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, there was no relationship between delay and lower socioeconomic status (Hackett et al, 1973;Worden and Weisman, 1975;MacAdam, 1979;MacArthur and Smith, 1984;Samet et al, 1988;Prohaska et al, 1990;Porta et al, 1996;Langenbach et al, 2003), although some studies suggested that this might be associated with increased delay. Rural residence (Robinson et al, 1986;Bain et al, 2002) and lower levels of education (Marshall and Funch, 1986;Dent et al, 1990;Vineis et al, 1993;Porta et al, 1996;Mariscal et al, 2001;Cockburn et al, 2003;McCaffery et al, 2003) were both found to increase delay.…”
Section: Patient Characteristicsmentioning
confidence: 99%